Literature Review: Faktor Pengaruh Wirausaha dalam Perspektif Psikologi - Alim, Janet Kurniawan; Made Swasti Wulanyani, Ni (Green Publisher Indonesia, 2024)
ASEAN Economic Community or ussualy called AEC are economic integration agenda by country in the ASEAN. AEC contribute huge impact on economic sector in Indonesia, but also gave both hope and challenge to people in Indonesia. AEC cause Indonesian workers need to compete harder with foreign workers, because that make the jobs offer more and more limited than before. Entrepreneurship is an activity that can create new jobs so that entrepreneurship is one answer to the problem of increasingly limited job opportunities. This article reviews previous research and articles with similar themes with the aim of providing an overview of the influencing factors of entrepreneurship from a psychological perspective. Based on several literature studies, it is concluded that there are various internal and external factors that influence entrepreneurship. Further research and studies are needed in the fields of psychology and entrepreneurship.